The Language of Shophouse Plans: Experimental Derivations with a Peranakan Grammar - Datta, Sambit; Tan, M. (2016)
This chapter presents the computational generation of abstract housing layouts based on a traditional urban housing typology: the shop-house architecture of Southeast Asia. This chapter explains the language of shophouse plans constructed across Southeast Asia between 1840 and 1960. The Chapter engages current research questions, the analysis and generation of collective form using computer-based methods of representation, simulation and generation. The chapter focuses on developing a formal computational description to model the structure of Shophouse plans. This chapter addresses the formal continuities embedded in the informal and eclectic language associated with this type of vernacular form in Asia. To capture this, the Chapter describes the key components of a shophouse plan, including the five-foot way, the main work and living spaces, ventilation, circulation and service elements. The three elements, a shape representation, combination rules and interpreter, comprise a “Peranakan Grammar” for deriving traditional shophouse layouts. A scheme for representing shapes is modeled using the set grammar generative design formalism. Secondly, the Chapter shows how these elements can be represented as rules of spatial combination. A Peranakan Grammar is then defined using the shape representation scheme to explore the distinctive layouts of pre-war shop-house layouts in Singapore. Finally, by applying these rules, shophouse plans are experimentally derived using a computer program, a grammar interpreter. Sample derivations of shop-house layouts in the language of the grammar are presented. The outcomes of the experimental derivation demonstrate that formal class description methods can be useful in describing cultural, place-specific productions of vernacular architecture. The Chapter ends with a discussion on the value of experimental computer generated approach to understanding the formal structure of vernacular architectural production in Southeast Asia.